SELF-ACUPRESURE DAN RAMUAN HERBAL UNTUK PENDERITA HIPERTENSI DI PUSKESMAS WONOKERTO 1 KABUPATEN PEKALONGAN - Yuniarsih, Sri Mumpuni; Hasanah, Nunung; Martani, Rahajeng; Afifah, Umul (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2024)
The prevalence of hypertension in Indonesia is still very high. The government has made various efforts to reduce the incidence of hypertension or prevent complications of hypertension. One of the efforts made is the Prolanis program implemented at the Puskesmas. Activities carried out in Prolanis include education on the care of patients with chronic diseases such as self-acupressure and herbal ingredients. self-acupressure is a massage technique at a certain point to help overcome various health problems and disease complaints, while herbal ingredients are all forms of traditional medicine that have been used for generations and have proven safe to overcome various specific health problems. The method used in this community service is self-acupressure training and making safe herbal concoctions for people with hypertension so that they can be applied at home safely by referring to a book published by the Ministry of health. The massage is done in the area of the head, shoulders, back of the hands, and back of the feet with a pressing motion for approximately 30 counts The herbs given were honey and nutmeg as well as gotu kola and garlic. The results of this community service were 16 participants with hypertension who received independent acupressure training and made herbal concoctions to reduce head pain and improve the quality of sleep of hypertensive patients. Most of the participants were female (87.5%), with a pre-elderly age category of 62.5%. A total of 37.5% were in the category of grade 2 hypertension with most experiencing mild headache (43.75%) and mild sleep disturbances (37.5%). This activity implies that participants get simple skills in self-care of hypertensive patients that are easy, cheap, and safe to overcome some of the symptoms that often appear, namely headache and sleep disturbances. Recommendations that can be given are integrated services between programs at the puskesmas, in this case, the traditional health service program and the disease control program, so that patients are exposed to traditional treatment methods in addition to conventional treatment.